Enhanced Annotation of Educational Video Resources for E-Learning - V. Kavitha Chandrakanth, Mrs.; Latha Parthiban, Dr. (International Journal of Engineering and Technology, 2018)
Educational video resources provides better scope for e-learners. Maximum number of present video resources lack in efficient annotation of video resources. This paper presents a novel methodology of annotating the videos in secured and isolated way by two annotating tools: annotation and synote tool. Annotation guides a way to browse user semantically and syntactically the web information which are available in Linked Data Open Cloud. Synote enables the user to retrieve the accurate and knowledgeable resource from semantic web. The paper concludes with applying linked open data cloud for annotation ofvideo resources which will be a scalable and reusability technology for future. Â